Effects of shredded waste paper as an additive on properties of concrete and structural behaviour of reinforced concrete beam - Solahuddin, Azuwa (2022)
Effective Waste Paper (WP) recycling is an alternative approach to reduce the rising disposal of WP and limiting landfills area. Some of these approaches are incorporating an additive in concrete mixtures to produce eco-friendly concrete for construction applications, subsequently reducing the cost of construction and preserving the fast-depleting forest and natural resources. Previous studies showed concrete with WP has greater compressive and flexural strength compared to concrete without WP, which could potentially replace Portland cement in concrete manufacturing. Nevertheless, the significance of Shredded Waste Paper (SWP) has not been fully evaluated in concrete mixture and RCB development. Therefore, this research investigated the effect of two types of SWP comprising Shredded Copier Waste Paper (SCPWP) and Shredded Cardboard Waste Paper (SCBWP) as additives on the concrete properties and the behaviour of Reinforced Concrete Beam (RCB). A total of seven concrete mixes were prepared with 0% (control), 5%, 10% and 15% addition of SCPWP and SCBWP, respectively, while three Shredded Waste Paper Reinforced Concrete Beams (SWPRCB) mixes were prepared with the addition of the optimum percentage of SCPWP and SCBWP based on optimum compressive strength. The Grade 30 concrete with a designated mixture of 1:0.75:1.5 (cement:sand:aggregate) and a water-to-cement (W/C) ratio of 0.5 was used in this study. The workability of fresh concrete and mechanical properties, such as compressive strength, flexural strength, splitting tensile strength and water absorption, were analysed after 7 and 28 days of water curing. It was found that the workability, compressive, flexural and splitting tensile strengths increased with 5% and 10% addition of SCPWP and SCBWP. Additionally, the water absorption increased with the higher addition of SCPWP and SCBWP. Contrarily, 15% of SCPWP and SCBWP addition recorded the highest water absorption and mass loss. The higher the percentage of SCPWP and SCBWP, the higher the water absorption rate. The concrete with SCBWP showed better strength and water absorption than SCPWP counterparts of similar addition percentages. The 10% addition of SWP was considered as the optimum percentage to achieve the highest compressive strength and was applied in the preparation of SWPRCB, which consisted of 0% C (control with no SWP), 10% SCPWP and 10% SCBWP. All specimens were air recured for 28 days with wet gunny sacks covering the SWPRCB’s top surface. The addition of 10% SCPWP and 10% SCBWP improves the structural behaviour, including the load at yield (Py), ultimate load (Pu), maximum load (Pmax), load at first crack (P1) and decreased the yield deflection (δy), ultimate deflection (δu) and maximum deflection (δmax) with full and reduced shear reinforcements with Stirrup Spacing (SS) = 100 mm, 150 mm, 200 mm than 0% C. Furthermore, the concrete bending and shear strains also increased with the addition of 10% SCPWP and 10% SCBWP for all shear reinforcements. As expected, the SWPRCB with SS = 200 mm recorded the highest concrete bending and shear strains. Nevertheless, 10% SCBWP achieved the lowest δy, δu and δmax compared to 10% SCPWP and 0% C. This study indicates that SCPWP and SCBWP gave optimum behaviour with 5% and 10% addition for concrete and 10% for RCB with significant strength and structural improvement.